Developing the quality seed production technology for berseem (Trifolium alexandrinum L.) fodder - Gondal, M. R.; Rizvi, S. A.; Hanif, M. S.; Mahmood, T.; Naseem, W.; Hayat, S.; Mustafa, S.; Pervez, A.; Khan, A. (International Journal of Agricultural Technology, 2021)
Berseem (Trifolium alexandrinum L.) is an important fodder crop of the region because of its palatability and nutritious nature that offers fodder in repeated cuttings almost year round. Under this study, effect of climatic variations and temporal cutting intervals on fodder production, seed vigor, seed yield and net income was assessed. The results showed significant variations in the period of flowering as well as yield characters under different cutting arrangements. Quality and production of seed reduced while the fodder tonnage increased with delaying the last cut for fodder. It was observed that last cutting taken on 20th April gave more fodder yield but low seed yield and thus income. Last cutting of Agaiti berseem taken on 10th March, Super late & Punjab berseem produced significantly higher number of seed per head, seed yield, 1000 grain weight and number of tillers m-2 on 20th March. It was concluded that all three varieties gave optimum production of quality seed while taking the last cut between 10th & 20th March with minimum temperature ranging from 8.66-22.33 oC, maximum temperature ranging from 25.91-39.79 ℃ and relative humidity of 64.40% to 46.30%